Sperm Cryopreservation Of Tropical Oyster, Magallana Bilineata (Röding, 1798) - Geraldine, Olive Chang Ju Lien (2019)
Unpredictable monsoon seasons can disrupt the production of commercially farmed oyster in Malaysia by altering the synchronization of gamete production. To better preserve the oyster farming industry in Malaysia for continuous production, an oyster storage seed bank could be a viable solution in the near future. Cryopreservation was carried out on the sperm of tropical oyster Magallana bilineata (Röding, 1798). M. bilineata sperm was diluted with a modified Ringer’s solution to 25 psu 1 μm filtered seawater ratio of 1:3. 200 μL M. bilineata sperm was added with two permeable (Glycerol and Dimethylsulfoxide (DMSO)) and non-permeable (Glucose and Sucrose) cryoprotectants (CPA) in four concentrations (5%, 10%, 15%, 20%) at the sperm to CPA ratio of 1:1, 1:3 and 1:5 to study its effects in two freezing methods; a. 10 mins in Ethanol-dry ice bath only and, b. 10 mins in Ethanol-dry ice bath and immediately into Liquid nitrogen). The control experiment was 200 μL fresh sperm to 25 psu 1 μm filtered seawater used in place of CPA at the ratios of 1:1, 1:3 and 1:5. The frozen sperm was thawed at 40°C in a water bath and was then fertilized with fresh M. bilineata oocytes. Viability assessment was carried out via Eosin-Nigrosin staining on sperm and observed under 1000x magnification on a light microscope. The highest post-thaw sperm viability was found in the control (68.72±8.47%). The 1:3 sperm to CPA ratio experiments yielded the highest viability among the other sperm: CPA ratios. The highest viability by CPA are 35.76±5.04% (DMSO 5%), 31.98±7.75% (Glycerol 10%), 16.23±6.65% (Glucose 5%) and 5.01±2.93% (Sucrose 10%), all of which are significantly lower than the control (P<0.05).